Values Ngudi Kasampurnan Sunan Kalijaga As A Basis of Religious Moderation Education - Edris Zamroni; Gudnanto Gudnanto; Indah Lestari; Muslihati Muslihati (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Indonesia faces the challenge of infiltrating radical ideology, which tends to conflict and use religion to divide national life. This research explores the values "ngudi kasampurnan" taught by Sunan Kalijaga to serve as a basis for strengthening religious moderation in the education system. The research method used is hermeneutic-phenomenological based on the Suluk Linglung Sunan Kalijaga manuscript and the teachings still adhered to by his descendants and students (the Demak community). To maintain the objectivity of the researcher's interpretation, this research involved resource persons competent in "suluk" analysis, suluk researchers, and practitioners of Sunan Kalijaga's teachings. The results show that philosophically, the values "ngudi kasampurnan" teach about restoring the understanding of humans as creatures who must not feel the most righteous and superior among others, regulating mental balance as the psychological basis of education, prioritizing manners and morals as the sociological basis of education, and preserving and developing the nation's noble traditions as a cultural basis. The implication is in packaging education that is friendly to differences in religion and belief, even in practices based on specific schools of thought or community organizations.